microRNAs and genetic diseases - Nicola Meola; Vincenzo A. Gennarino; Sandro Banfi (2009)
microRNAs (miRNAs) are a class of small RNAs (19-25 nucleotides in length) processed from double-stranded hairpin precursors. They negatively regulate gene expression in animals, by binding, with imperfect base pairing, to target sites in messenger RNAs (usually in 3' untranslated regions) thereby either reducing translational efficiency or determining transcript degradation. Considering that each miRNA can regulate, on average, the expression of approximately several hundred target genes, the miRNA apparatus can participate in the control of the gene expression of a large quota of mammalian transcriptomes and proteomes. As a consequence, miRNAs are expected to regulate various developmental and physiological processes, such as the development and function of many tissue and organs. Due to the strong impact of miRNAs on the biological processes, it is expected that mutations affecting miRNA function have a pathogenic role in human genetic diseases, similar to protein-coding genes. In this review, we provide an overview of the evidence available to date which support the pathogenic role of miRNAs in human genetic diseases. We will first describe the main types of mutation mechanisms affecting miRNA function that can result in human genetic disorders, namely: (1) mutations affecting miRNA sequences; (2) mutations in the recognition sites for miRNAs harboured in target mRNAs; and (3) mutations in genes that participate in the general processes of miRNA processing and function. Finally, we will also describe the results of recent studies, mostly based on animal models, indicating the phenotypic consequences of miRNA alterations on the function of several tissues and organs. These studies suggest that the spectrum of genetic diseases possibly caused by mutations in miRNAs is wide and is only starting to be unravelled.